The importance of policy in perceptions of organizational justice - Brown, Graham; Bemmels, B.; Barclay, L. (Plenum Publishing Corporation, 2010)
Organizations create policies in an effort to reduce injustice, as well as address the needs and interests of organizational members. We argue that individuals can make fairness judgments related to organizational policies, which are independent from other dimensions of fairness (i.e. distributive, procedural, interpersonal, and informational justice). Results of a field study with 164 union members found that (a) individuals make judgments about the fairness of policies that are distinct from other forms of justice, (b) perceptions of policy justice predict variance in behaviors beyond other forms of justice, and (c) perceptions of policy justice interact with distributive and procedural justice to predict behaviors. More specifically, results show that policy justice interacts with distributive justice to predict turnover intentions and citizenship behaviors towards the union. Policy justice also interacts with procedural justice to predict turnover intentions. However, this interaction was in the opposite direction from what we originally predicted. We discuss the implications of these findings for justice research and practice, as well as provide avenues for future research. © The Author(s) 2010.